(untitled) (Dermatology Reports, 2023)
The development of flares or new-onset of immune-mediated dermatologic diseases, including psoriasis, has occurred with the worldwide spreading of the COVID-19 pandemic. We report the case of a 38-year-old woman who came to our department with a severe flare of plaque psoriasis four weeks after SARS-CoV-2 infection. Her Psoriasis Area Severity Index was 25, and her Dermatology Life Quality Index was 18. Our initial decision was to prescribe acitretin, but the patients reported adverse events. For this reason, we started risankizumab with complete skin clearance after 16 weeks. The patient is still on treatment, and no adverse events have been reported to date.